Contributi per una flora vascolare di Toscana. VIII (440-506) - Peruzzi, Lorenzo; Viciani, Daniele; Agostini, Nevio; Angiolini, Claudia; Ardenghi, Nicola M. G.; Astuti, Giovanni; Bardaro, Maria Rosaria; Bertacchi, Andrea; Bonari, Gianmaria; Boni, Sara; ChytrÃ1⁄2, Milan; Ciampolini, Fabrizio; et al. (Societa Toscana di Scienze Naturali, 2016)
New localities and/or confirmations concerning 67 specific and subspecific plant taxa of Tuscan vascular flora, belonging to 59 genera and 37 families are presented: Alisma (Alismataceae), Amaranthus (Amaranthaceae), Leucojum, Sternbergia, Tristagma (Amaryllidaceae), Aloe (Asphodelaceae), Erigeron, Galinsoga, Hieracium, Rhagadiolus, Silybum, Soliva, Taraxacum (Asteraceae), Impatiens (Balsaminaceae), Berberis (Berberidaceae), Cardamine (Brassicaceae), Opuntia (Cactaceae), Cephalaria, Sixalix, Succisa (Caprifoliaceae), Silene (Caryophyllaceae), Convolvulus, Ipomoea (Convolvulaceae), Aeonium (Crassulaceae), Scirpus (Cyperaceae), Equisetum (Equisetaceae), Euphorbia (Euphorbiaceae), Astragalus, Trifolium (Fabaceae), Quercus (Fagaceae), Crocus (Iridaceae), Juncus (Juncaceae), Utricularia (Lentibulariaceae), Peplis (Lythraceae), Maclura (Moraceae), Nymphaea (Nymphaeaceae), Oenothera (Onagraceae), Anacamptis, Orchis (Orchidaceae), Orobanche (Orobanchaceae), Callitriche, Veronica (Plantaginaceae), Alopecurus, Eleusine, Glyceria, Phleum (Poaceae), Persicaria, Polygonum (Polygonaceae), Groenlandia (Potamogetonaceae), Clematis, Pulsatilla, Ranunculus (Ranunculaceae), Rhamnus (Rhamnaceae), Fragaria, Potentilla, Pyracantha (Rosaceae), Galium (Rubiaceae), Sparganium (Typhaceae), Vitis (Vitaceae). In the end, the conservation status of the units and eventual protection of the cited biotopes are discussed.